THEORY OF PARTS OF THE SENTENCE: PRINCIPLE, SECONDARY PARTS OF THE SENTENCE, PROBLEMS OF TERTIARY - Teshaboyeva Nafisa Zubaydulla qizi; Sheraliyeva Shoira To’lqin qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article explores the theory of sentence structure by categorizing sentence components into principal, secondary, and tertiary parts. The principal parts—subject and predicate—form the essential core of any sentence, establishing its fundamental meaning. Secondary parts, including objects, attributes, and adverbial modifiers, add specificity and depth, allowing for detailed expression. The concept of tertiary parts, though less defined in traditional grammar, includes parenthetical expressions, disjoints, and embedded clauses that provide additional context and stylistic nuance. The boundaries between secondary and tertiary parts remain a subject of debate, as tertiary elements are non-essential yet often enrich the tone and viewpoint of a sentence. This analysis of sentence structure offers a framework for understanding how language conveys both core meaning and contextual subtleties, highlighting the complex interaction between syntactic components.